Socio-economic Effects of Flood Among Rural and Urban Farm Families in Flood-prone Areas of Imo State, Nigeria - Chikaire, J.U; Ejiogu, C.C; Osuji, M.N; Ogueri, C.,; 4Anyanwu, C.N; 5Ihem, E.E; Aririguzo, B.N; Ojiaku, A.A; Godson–Ibeji, C.C; Nwaiwu, I.U.O; et al. (The Bioscan, 2025)
This study investigated the socio-economic damages caused by floods in Imo State, Nigeria. A total of 650 farm families were selected randomly and purposively from Flood-prone communities of Imo State, Nigeria. The questionnaire was used to collect information on the causes of floods, damages, control measures, and challenges to the control of floods. Descriptive tools of measurement were used to analyze data. It was found that floods occurred concurrently in most communities from 1999 till year 2024. Floods occur due to two factors: natural causes and human causes of floods. Natural causes include prolonged heavy rainfall (M=3.80), climate change (M=2.78), low-lying topography (M=2.76), among others. The human causes include poor land use (M=3.25), increased urbanization (M=2.44), and blockade of waterways (M=3.05), among other causes. Flood control measures adopted include the construction of embankments (98%), tree planting (88.3%), digging trenches (92.9%), and relocation to safer places (98.6%), among other measures. However, they faced challenges adopting flood control measures, such as fear of being carried by water, low education, and lack of financial support, among other issues. Heavy flood has numerous life-threatening effects classified as environmental, infrastructural, and socio-economic. The infrastructural effects are destruction of utility works and social amenities (98.4%), homelessness and temporary dislocation (96.1%), interruption of the transport system (99.6%), damages to schools’ buildings (81.1%) and hospitals, loss of properties, damage to rural and urban roads and many more. The environmental effects of floods include loss of soil nutrients (93.8%), pollution of the environment (96.1%), loss of biodiversity (92.6%), leads to epidemics (89.3%), soil infiltration (76.6%), damages to water quality and quantity (94.9%) and many more. Socio-economic effects include loss of farm crops and farmland (99.5%), hunger and starvation (98.2%), poverty (90.2%), poor health status (94.1%), death of farm animals, damages to aquatic life, and the ultimate loss of human lives.